PERFORMANCE EVALUATION OF ASPHALTIC CONCRETE WEARING COURSES (AC-WC) USING CRUMB RUBBER AS AN ADDITIVE - Syahputra, Deka
This study aims is to measure the performance of a mixture of Asphalt Concrete - Wearing Course (AC-WC) with addition of crumb rubber using a dry process, where crumb rubber as an aggregate substitution of fraction no. 50 at variations of 0%, 25%, and 50% by weight. The method used in this research is the experimental method in the laboratory. Primary data collection is done through testing of aggregates, asphalt, crumb rubber, and mixtures. Hot mix design used Marshall test to obtain Optimum Bitumen Content (OBC). Laboratory test in OBC conditions obtain consist of Resilient Modulus test used Dynamic Testing System (DTS) at 25°C, 35°C, and 45°C and rut depth test used Hamburg Wheel Tracking (HWT) at temperatures 45°C and 60°C. The results of addition of crumb rubber content to the mixture increase the value of OBC and reduce the value of Marshall stability, the percentage of 50% crumb rubber obtained highest OBC is 6.5% and the lowest Marshall stability is 1191.854 kg. The crumb rubber content in the mixture lowers the value of Modulus Resilient, AC-WC with 0% crumb rubber has the highest value (respectively, each temperature is 4,273 MPa, 1,728 MPa, and 525 MPa). At a temperature of 60°C, 25% crumb rubber content in the mixture reduces the rut depth value which is 3.00 mm, the highest value of Stripping Inflection Point and creep slope (respectively, 2,600 passes and 781 passes/mm ). Based on the Marshall stability, Resilient Modulus, and rut depth values, then the crumb rubber content to replace aggregate fraction no. 50 in the AC-WC gives the highest value is 25% in laboratory test.